2018
DOI: 10.3390/ijms19113339
|View full text |Cite
|
Sign up to set email alerts
|

The Role of PPAR-δ in Metabolism, Inflammation, and Cancer: Many Characters of a Critical Transcription Factor

Abstract: Peroxisome proliferator-activated receptor-delta (PPAR-δ), one of three members of the PPAR group in the nuclear receptor superfamily, is a ligand-activated transcription factor. PPAR-δ regulates important cellular metabolic functions that contribute to maintaining energy balance. PPAR-δ is especially important in regulating fatty acid uptake, transport, and β-oxidation as well as insulin secretion and sensitivity. These salutary PPAR-δ functions in normal cells are thought to protect against metabolic-syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(99 citation statements)
references
References 99 publications
0
99
0
Order By: Relevance
“…Many studies using different cell models have been published afterwards. Several aspects of PPARβ/δ function with relevance for cancer growth have been reviewed recently [1,5,6,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies using different cell models have been published afterwards. Several aspects of PPARβ/δ function with relevance for cancer growth have been reviewed recently [1,5,6,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…PPARδ inhibits VSMCs proliferation through suppressing cyclin D1 and cyclin-dependent kinase 4, and inducing cyclin-dependent kinase inhibitor p21 and p27 [44] . PPARδ contributes to anti-inflammation and anti-apoptosis effects and suppresses cellular migration in metabolic diseases by inhibiting IL1β [45] . In diabetic mice, the phosphorylation of STAT3 is suppressed by PPARδ or its agonist GW501516 which blocks inflammation in adipocytes and hepatocytes [46] .…”
Section: Discussionmentioning
confidence: 99%
“…PPARd is an unsaturated fatty acid receptor, expresses in most cells including skeletal muscle and macrophages, and acts as a critical regulator of cellular energy expenditure. Its activation can suppress inflammation, reduce lipase activity, and inhibit low density lipoprotein production (Liu et al, 2018). It has been reported that PPARd regulated fatty acid transport, b-oxidation, and mitochondrial respiration (Wang et al, 2003).…”
Section: Discussionmentioning
confidence: 99%